Herramienta para la gestión de auditorías internas basado en la norma ISO 9001:2015 (2016)
This work aims to plan the quality management system based on the requirements of ISO 9001: 2015 in the commercial area of ​​a company dedicated to import and distribute products for laboratory. First, a diagnosis of the current state of the business area of ​​the company in relation to compliance with the requirements of the standard is presented. Subsequently, an analysis of the context is carried out by means of the SWOT tool and the vester matrix. Finally, the process map and the characterization of the mission processes associated with the business area of ​​the company are established.